2014
DOI: 10.5455/jihp.20140512102819
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Mast Cells and Eosinophils Counts in Surgically Resected Appendix

Abstract: Objectives: The mast cell remains an enigmatic cell, found resident in tissues throughout the body particularly in association with structures such as blood vessels and nerves. Various inflammatory disorders of the intestines, joints and lungs appear to be associated with an increase in mast cell numbers. The study was conducted on vermiform appendix. The present study was undertaken (1) to compare the mast cell and eosinophil counts in various layers of the appendix in various histopathological groups, and (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 6 publications
7
29
2
Order By: Relevance
“…In the present study the mean mast cell count was found to be highest in mucosa followed by submucosa and then muscularis propria, but study by Verma A et al [13] found that mast cells were more easily identified in submucosa. In comparison of the findings in the present study and study by Kolur A et al [7], mean mast cell count was highest in chronic appendicitis, followed next in frequency by acute appendicitis and acute suppurative appendicitis compared to normal / unremarkable appendix and the mean mast cell count in chronic appendicitis and acute appendicitis was highest in the mucosa, followed by submucosa and muscularis propria in Kolur A et al [7] study, these results were in concordance with the present study. [7] showed few contrary results with the present study, where they found the mean mast cell count in acute suppurative to be highest in muscularis propria followed by mucosa then submucosa, however in the present study the mean mast cell count was found to be highest in the mucosa, followed by submucosa then muscularis propria.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study the mean mast cell count was found to be highest in mucosa followed by submucosa and then muscularis propria, but study by Verma A et al [13] found that mast cells were more easily identified in submucosa. In comparison of the findings in the present study and study by Kolur A et al [7], mean mast cell count was highest in chronic appendicitis, followed next in frequency by acute appendicitis and acute suppurative appendicitis compared to normal / unremarkable appendix and the mean mast cell count in chronic appendicitis and acute appendicitis was highest in the mucosa, followed by submucosa and muscularis propria in Kolur A et al [7] study, these results were in concordance with the present study. [7] showed few contrary results with the present study, where they found the mean mast cell count in acute suppurative to be highest in muscularis propria followed by mucosa then submucosa, however in the present study the mean mast cell count was found to be highest in the mucosa, followed by submucosa then muscularis propria.…”
Section: Discussionsupporting
confidence: 92%
“…In comparison of the findings in the present study and study by Kolur A et al [7], mean mast cell count was highest in chronic appendicitis, followed next in frequency by acute appendicitis and acute suppurative appendicitis compared to normal / unremarkable appendix and the mean mast cell count in chronic appendicitis and acute appendicitis was highest in the mucosa, followed by submucosa and muscularis propria in Kolur A et al [7] study, these results were in concordance with the present study. [7] showed few contrary results with the present study, where they found the mean mast cell count in acute suppurative to be highest in muscularis propria followed by mucosa then submucosa, however in the present study the mean mast cell count was found to be highest in the mucosa, followed by submucosa then muscularis propria. Increase in mast cells in acute appendicitis together with the broad spectrum of activities of mast cell derived mediators was seen in studies done by Sonti S [8], Sharma J et al [14], Kumaran C et al [15] and Bhramarambha K et al [11].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Appendicular sections were sampled from the tip, base and intermediate length for fixation and paraffin processing. Two sections of 5-micron thickness were cut from each paraffin block and stained by hematoxylin & eosin (8). The criteria for AA was polymorphous nuclear neutrophils infiltration at the muscularis propria (9).…”
Section: Pathologic Analysismentioning
confidence: 99%